2024
DOI: 10.1051/0004-6361/202349025
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the rise of supermassive black holes

Irham T. Andika,
Knud Jahnke,
Masafusa Onoue
et al.

Abstract: We report the identification of 64 new candidates of compact galaxies, potentially hosting faint quasars with bolometric luminosities of $L_ bol $--1046 erg s$^ $, residing in the reionization epoch within the redshift range of $6 z 8$. These candidates were selected by harnessing the rich multiband datasets provided by the emerging JWST-driven extragalactic surveys, focusing on COSMOS-Web, as well as JADES, UNCOVER, CEERS, and PRIMER. Our search strategy includes two stages: applying stringent photometric cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 145 publications
2
1
0
Order By: Relevance
“…But observations will be challenging, since we predict that this occurs on short time and small spatial scales in high-redshift systems, with comparable stellar and BH accretion bolometric luminosity, and the medium is still dusty and obscured at these times owing to the high gas densities. Still, it is immediately striking that the bolometric luminosities (∼5-50 × 10 44 erg s −1 , depending on the BH radiative efficiency), sizes (∼10-100 pc), broadly comparable mix of stellar and active galactic nucleus luminosity, and colors (given the predicted dust column densities at large radii from Figure 4) this simulation would exhibit during its later evolution (0.7 Myr, after coalescence and disk formation) are all remarkably consistent with the observed properties of the unexpected population of "little red dots" seen by JWST at redshifts z ∼ 4-10 (compare, e.g., Andika et al 2024;Kocevski et al 2024;Kokorev et al 2024).…”
Section: Discussionsupporting
confidence: 77%
“…But observations will be challenging, since we predict that this occurs on short time and small spatial scales in high-redshift systems, with comparable stellar and BH accretion bolometric luminosity, and the medium is still dusty and obscured at these times owing to the high gas densities. Still, it is immediately striking that the bolometric luminosities (∼5-50 × 10 44 erg s −1 , depending on the BH radiative efficiency), sizes (∼10-100 pc), broadly comparable mix of stellar and active galactic nucleus luminosity, and colors (given the predicted dust column densities at large radii from Figure 4) this simulation would exhibit during its later evolution (0.7 Myr, after coalescence and disk formation) are all remarkably consistent with the observed properties of the unexpected population of "little red dots" seen by JWST at redshifts z ∼ 4-10 (compare, e.g., Andika et al 2024;Kocevski et al 2024;Kokorev et al 2024).…”
Section: Discussionsupporting
confidence: 77%
“…For example, in GOODS-S, Matthee et al (2024) report an average σ z = |Δz|/(1 + z spec ) = 0.01, and UNCOVER LRDs presented in Greene et al (2024) have shown σ z ∼ 0.04. A similar consistency was also found between the initial photometric source selection and final spectra in the JADES and CEERS fields (Kocevski et al 2023;Andika et al 2024;Maiolino et al 2024). As such, we consider that utilizing EAZY to derive redshifts is adequate for our sample.…”
Section: Photometric Redshiftssupporting
confidence: 77%
“…Using observed NIR colors to pick out active BHs in extragalactic fields is by no means a novel endeavor and has already been successfully done with the IRAC instrument on board the Spitzer Space Telescope (Lacy et al 2004;Stern et al 2005;Donley et al 2012). This method, however, is still in its infancy when it comes to JWST (Labbé et al 2023a;Andika et al 2024). As already pointed out by Matthee et al (2024), very few JWST programs that detect dusty AGN were actually designed with AGN in mind, implying that there is still more that we can do to address a growing number of questions about this population.…”
Section: Final Remarksmentioning
confidence: 99%